Penerapan Metode Bercerita untuk Meningkatkan Pemahaman Siswa tentang Kisah Nabi dan Rasul di Kelas II SDN 3 Mamben Daya - Syamsur Rizal (Jurnal Ilmu Pendidikan, 2025)
Elementary school students' understanding of the stories of the Prophets and Apostles is an important part of forming religious and moral character. However, in reality, many students have difficulty understanding the material when delivered conventionally. Based on this, this study aims to determine the effectiveness of the application of the storytelling method in improving the understanding of grade II students of SDN 3 Mamben Daya regarding the stories of the Prophets and Apostles. This study uses a qualitative approach with a classroom action research (CAR) design which was carried out for six months, from January to June 2024. The research subjects were 29 students, consisting of 16 males and 13 females. Data collection techniques were carried out through observation, learning outcome evaluation tests, and open interviews. The results of the study showed that the application of the storytelling method was able to significantly improve students' understanding. This can be seen from the increase in the average student score from 68.3 in cycle I to 84.7 in cycle II, as well as the increase in student involvement in learning. Interviews with teachers and students also confirmed that this method makes learning more interesting and makes it easier to understand the contents of the story. Thus, it can be concluded that the storytelling method is effective in Islamic Religious Education learning, especially to convey religious stories that are narrative in nature and contain moral values. This method also has the potential to be used more widely in early elementary school classes.